2022
DOI: 10.34172/cjmb.2023.03
|View full text |Cite
|
Sign up to set email alerts
|

Do Educated Women Have More Sexual Satisfaction? A Systematic Review Study

Abstract: Objectives: Educational status affects all aspects of life, including sex life. Regarding the relationship between women’s sexual satisfaction and their education level, contradictory results have been obtained so far. This systematic review aimed to summarize the existing knowledge in this area. Methods: In this study, three electronic databases, including PubMed, Scopus, and Web of Science were searched for all the related articles published from 1 January, 2000 to 28 June, 2022. The MeSH keywords including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Therefore, providing social and psychological support for victims can lead to lower and less severe consequences on domestic violence victims (43). Moreover, research has shown that raising awareness and utilizing cognitive behavioral therapy and psychological counseling for women can reduce the severity of psychological symptoms, such as depression and anxiety (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, providing social and psychological support for victims can lead to lower and less severe consequences on domestic violence victims (43). Moreover, research has shown that raising awareness and utilizing cognitive behavioral therapy and psychological counseling for women can reduce the severity of psychological symptoms, such as depression and anxiety (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Bayat et al found that therapeutic massage could decrease FBS and HbA1c. Also, it could help in improving neuropathic pain in patients with diabetic neuropathy [130].…”
Section: Therapeutic Massagementioning
confidence: 99%
“…Natural remedies can be contaminated with substances like pesticides, heavy metals, or microbes, posing health risks. For example, some Ayurvedic herbal products in the US have been found to contain harmful substances [70]. It is often not regulated or monitored, leaving users vulnerable to risks such as adulteration, contamination, toxicity, and interactions with other drugs or foods [68,70].…”
Section: Challengesmentioning
confidence: 99%
“…For example, some Ayurvedic herbal products in the US have been found to contain harmful substances [70]. It is often not regulated or monitored, leaving users vulnerable to risks such as adulteration, contamination, toxicity, and interactions with other drugs or foods [68,70]. Natural remedies can vary in composition, quality, potency, and purity due to factors like sourcing, harvesting, processing, and storage conditions.…”
Section: Challengesmentioning
confidence: 99%